2010
DOI: 10.1016/j.anifeedsci.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ruminal fermentation kinetics and energy utilization of three Mexican tree fodder species during the rainy and dry period

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
5
11
0
1
Order By: Relevance
“…Compared with the values reported in this study, Camacho et al. () reported similar values of CP, NDF and ADF for P. dulce during wet and dry seasons in a region near to the present study site. The CP content of the three browse tree species used in our study indicated that they provide ruminal degradable N when used as supplements during the dry season in semi‐arid regions.…”
Section: Discussionsupporting
confidence: 84%
“…Compared with the values reported in this study, Camacho et al. () reported similar values of CP, NDF and ADF for P. dulce during wet and dry seasons in a region near to the present study site. The CP content of the three browse tree species used in our study indicated that they provide ruminal degradable N when used as supplements during the dry season in semi‐arid regions.…”
Section: Discussionsupporting
confidence: 84%
“…Also, the relatively high level of ADL in browse forages as shown in Table 1 explained in part the limited in vitro degradation and therefore the lower amount of gas produced. Similar observations were reported by Nordheim-Viken and Volden, [48,49]. McAllister et al [50] also observe that higher NDF and lignifications and/or higher ADF/NDF proportion and free-CT contents can reduce attachment of ruminal microbes to feed particles, as well as inhibit microbial growth and enzyme activity [44] or intestinal bacterial activity [46] by free-condensed tannins and hence lead to lower gas production.…”
Section: Discussionsupporting
confidence: 73%
“…On average, the effect of inoculum source on GP was more pronounced in browse species (114.8 ml/g OM), known for their phenolic/tannin composition, than for temperate feedstuffs (102.6 ml/g OM). The greater differences between cow and goat to ferment browse substrates were in line with results of Camacho et al (2010) who observed higher browse fermentation in vitro in goat inocula (128.4 ml/g DM) compared to cow inocula (104.7 ml/g DM) adapted to the same browse diet. Such peculiar characteristics may be related to the feeding habits or animal species specific adaptations.…”
Section: Discussionsupporting
confidence: 73%
“…The proportion of gas produced during the first phase (32.4 vs 28.9%) and third phase (21.3 vs 17.5%) was higher in goat inoculum compared to cows. Similarly, increased GP during the early hours of in vitro fermentation was also observed in goats compared to cow rumen inoculum (Camacho et al, 2010). Partitioning of gas production into different phases assists to understand fermentation characteristics of incubated feedstuff.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation